2014
DOI: 10.1186/1471-2334-14-422
|View full text |Cite
|
Sign up to set email alerts
|

Serological survey of Leishmaniainfection in blood donors in Salvador, Northeastern Brazil

Abstract: BackgroundVisceral Leishmaniasis is endemic to Brazil, where it is caused by Leishmania infantum (syn. Leishmania chagasi). Following parasite inoculation, individuals may experience asymptomatic infection, raising the possibility of parasite transmission through the transfusion of contaminated blood products. In the present work, we evaluated the prevalence of asymptomatic Leishmania infection among blood donors in Salvador, northeastern Brazil.MethodsPeripheral blood was collected from 700 blood donors atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 43 publications
(65 reference statements)
1
14
0
Order By: Relevance
“…The high prevalence of seropositivity to L. infantum in blood donors from the endemic regions in this study confirms data reported in the Brazilian literature (Luz et al, ; Urias et al, ; França et al, ; Fukutani et al, ). This prevalence is much higher than the sum of donors considered unfit for donation due to the seven blood‐transmissible diseases compulsorily tested in the country, which in 2013 was 3·64% (ANVISA – Agência Nacional de Vigilância Sanitária, Brazil, 2013).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The high prevalence of seropositivity to L. infantum in blood donors from the endemic regions in this study confirms data reported in the Brazilian literature (Luz et al, ; Urias et al, ; França et al, ; Fukutani et al, ). This prevalence is much higher than the sum of donors considered unfit for donation due to the seven blood‐transmissible diseases compulsorily tested in the country, which in 2013 was 3·64% (ANVISA – Agência Nacional de Vigilância Sanitária, Brazil, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…In this scenario, the transmission of parasites of the genus Leishmania occurs normally through the bite of phlebotomine sand flies. However, studies have shown parasite survival in different storage blood component preparations (Grogl et al, ; Cardo, ; Fukutani et al, ) and have also shown that the transfusion of contaminated blood products can be a source of disease transmission in parallel with the transplantation of organs (Desjeux, ; Silva et al, ; Mahesh et al, ).…”
mentioning
confidence: 99%
“…10 In the present study, none of the samples were positive in the rapid test, corroborating the results of other studies that reported low sensitivity rates for asymptomatic infections. 11 Therefore, tests based on rK39 are most useful when diagnosing active infection by Leishmania species.…”
Section: Discussionmentioning
confidence: 99%
“…The association of the clinical and epidemiological with the serological screening can improve the blood donor selection by detection of asymptomatic forms of diseases that are transmissible through blood. Fukutani et al (12) , detected Leishmania kinetoplast deoxyribonucleic acid (kDNA) minicircles in blood donors in an endemic area for visceral leishmaniasis, indicating that, in addition to antibodies, these asymptomatic individuals can harbors the parasite, representing risk of transmission to the recipient.…”
Section: Permanente De éTica Em Pesquisa Envolvendo Seres Humanos Unmentioning
confidence: 99%